Giant Seebeck effect in pure fullerene thin films. (18th November 2015) - Kojima, Hirotaka; Abe, Ryo; Ito, Mitsuhiro; Tomatsu, Yasuyuki; Fujiwara, Fumiya; Matsubara, Ryosuke; Yoshimoto, Noriyuki; Nakamura, Masakazu
Abstract: The small thermal conductivity of molecular solids is beneficial for their thermoelectric applications. If Seebeck coefficients were sufficiently large to compensate for the relatively small electrical conductivity, these materials would be promising candidates for thermoelectric devices. In this work, the thermoelectric properties of C60 were studied by in situ measurements under ultrahigh vacuum after the deposition of a pure C60 thin film. An exceptionally large Seebeck coefficient of more than 150 mV/K was observed as a steady-state thermoelectromotive force. Even considering several extreme but realistic conditions, conventional semiclassical thermoelectric theories cannot explain this giant Seebeck effect.